‘Let the Rain Fall Relentlessly’: Singing the Song of Survival - Newell, Christopher (Feminist theology, 2013)
This paper, a version of which was presented at the ‘Feminist Futures’ twentieth Anniversary conference of the British and Irish Feminist Theology Summer School in July 2012, is, in one sense, a misnomer. Through the lived experience of one remarkable woman with whom I have the privilege of working as a mental health chaplain and companion, I recount her past of pervasive patriarchal abuse, pain, and psychic ‘storms’ but also her present that contains her songs of survival and her language of liberation. It is one woman’s life, a life that could be replicated in many women’s lives, not only in the past, but in the present and throughout the world. But it is only by being acutely reminded of the unique, personal narratives of women, and men, whose past continues to invade our presents by their unbearable witness to the actual violence of the patriarchal landscapes in which their ‘voices’ have been seemingly silenced and their language pathologized, that we shall be able together to conceive of futures. These are futures where, whilst, acknowledging the continuing severe and enduring psychological damage to the abused and the violated and enabling appropriate treatment to be available, we shall also empower the bearing of the witness, the resolute and hard won language of the remaining, the bursting forth from the deadness of tombs of terror, of resurrected lives in the dance of the garden. This will require a sea-change in the way we imagine and establish mental health services and it will require an applied feminist theological methodology to be at the heart, not only of the theoretical models, but of the witnessing to the theology-making that such hidden, ‘anonymous’ lives intrinsically reveal. To imagine such mental health services is a subject for another paper. For now I want to introduce one such life I have been describing and with whom I have the privilege of travelling, consciously and shamefully aware of my gender in a way which seems OK, which seems re-imagined through the eyes of a woman who has absolutely no reason to love men but who has invited me to tread tenderly towards the sights and seasons of her pain and abuse.